ANALYSIS OF SCIENTIFIC APPROACHES TO CLASSIFICATION OF KEY COMPETENCIES - Belova, Julia A. (Educological discourse, 2014)
The article discusses approaches to the interpretation of the concept of "key competencies" in the scientific and educational literature; the analysis of existing methods of allocating a basic set of core competencies; presents various classifications of key competences.